High prevalence of itraconazole resistance among Candida parapsilosis isolated from Iran - Fozieh Hassanmoghadam; Tahere Shokohi; Mohammad Taghi Hedayati; Narges Aslani; Iman Haghani; Mojtaba Nabili; Ensieh Lotfali; Amirhossein Davari; Maryam Moazeni (Mazandaran University of Medical Sciences, 2019)
Background and Purpose: Candida parapsilosis isolates usually have a low minimum inhibitory concentration (MIC) against azoles. Although Candida parapsilosis isolates usually have low MICs against azoles, recent studies candida invasive infections due to azole resistant-C. parapsilosis isolates . Regarding this, the main aim of this study was to determine the susceptibility pattern of Iranian clinical C. parapsilosis against available azole antifungal drugs. Materials and Methods: This study was conducted on 105 previously-identified isolates of C. parapsilosis sensu stricto. For the purpose of the study, the isolates were subjected to antifungal susceptibility testing against fluconazole (FLZ), itraconazole (ITZ), voriconazole (VRZ), and two new azole drugs, namely luliconazole (LUZU) and lanoconazole (LZN). The broth microdilution reference method adopted in this study was according to the Clinical & Laboratory Standards Institute M27-A3 and M27-S4 documents. Results: According to the results, 89% (n=94) of C. parapsilosis isolates showed a MIC of ≥ 1 μg/ml, indicating resistance against ITZ. Multi-azole resistance was observed in 3.8% of the isolates. In addition, LUZU and LZN demonstrated the highest efficacy with the MIC50 values of 0.5 and 1 μg/ml, respectively. Conclusion: The majority of the isolates showed high MIC values against ITZ. This may have been associated with the long-term ITZ prophylaxis/therapy in patients infected with candidiasis. Hence, the adoption of an appropriate antifungal agent is a crucial step for starting the treatment. Background and Purpose: Although Candida parapsilosis isolates have usually low MICs against azoles but recent study confirmed Candida -related invasive infections due to azoles resistance C. parapsilosis isolates. The main aim of this study was to determine the susceptibility pattern of Iranian clinical C. parapsilosis against available azolesantifungal drugs. . Material and Methods: One hundred and five previously-identified isolates of C. parapsilosis sensu stricto were subjected to antifungal susceptibility testing against fluconazole, itraconazole, voriconazole and two new azole drugs, loliconazole and lanoconazole using the broth microdilution reference method according to CLSI M27-A3 and M27-S4 document. Results: Eighty nine percent (n=94) of C. parapsilosis isolates showed MIC ≥ 1µg/ml which indicated resistance against itraconazole. Multi-azoles resistances were observed in 3.8% of the isolates. Loliconazole and lanoconazole demonstrated the highest efficacy with MIC50 values of 0.5 and 1µg/ml, respectively. Conclusion: The majority of the isolates showed high MIC values against Itraconazole. It may associated with the long term Itraconazole prophylaxis/therapy in patients Infected with candidasis. Hence, choosing the appropriate antifungal is the crucial step for starting treatment.